Preparation and mechanical properties of (SiCnp+NiTip)/Al composites with triple-modal grain structure - Xue Zhang; Mingfang Qian; Xuexi Zhang; Lin Geng (Journal of Materials Research and Technology)
A controllable composite powder ball milling and assembly strategy were employed to achieve a tri-modal grain structure in silicon carbide (SiC) nanoparticles plus NiTi particles (SiCnp+NiTip)/Al composites. High-energy ball milling was used for SiCnp with small-sized pure Al powder, which formed ultrafine grains (UFG) smaller than 500 nm. NiTip and large-size pure Al powder use the same process as Al-SiCnp powder to forming 0.5–5 μm fine grains (FG). Large-size pure Al powder with coarse grains (CG, average grain size 9.4 μm) were mixed with Al-SiCnp and Al-NiTip powders via low energy ball milling. The mixed powders were spark plasma sintered (SPS) to prepare UFG-FG-CG tri-modal grain structure composites with superior strength-ductility synergy. For Com 35-35-30, the ultimate tensile strength (UTS) (285.7 ± 3.1 MPa) and elongation (δ) (10.5 ± 2.7%) were 25.6% and 228% higher than those of the homogeneous composite counterpart, respectively. These simultaneously enhanced strength and ductility were attributed to the good interfacial bonding strength of NiTi/Al and the back stress strengthening effect from the tri-modal grain structure design that meets the stress matching requirements of NiTip. Therefore, the step-wise ball milling of composite powders and their assembly have been demonstrated to be an effective technique for fabricating Al matrix nanocomposites with heterogeneous structures.